The role of coronary artery disease in lung transplantation: a propensity-matched analysis - Lüsebrink, Enzo; Gade, Nils; Seifert, Paula; Ceelen, Felix; Veit, Tobias; Fohrer, Fabian; Hoffmann, Sabine; Höpler, Julia; Binzenhöfer, Leonhard; Roden, Daniel; Saleh, Inas; Lanz, Hugo; et al. (Clinical research in cardiology, 2024)
Candidate selection for lung transplantation (LuTx) is pivotal to ensure individual patient benefit as well as optimal donor organ allocation. The impact of coronary artery disease (CAD) on post-transplant outcomes remains controversial. We provide comprehensive data on the relevance of CAD for short- and long-term outcomes following LuTx and identify risk factors for mortality.